1977
DOI: 10.1073/pnas.74.6.2475
|View full text |Cite
|
Sign up to set email alerts
|

Globin RNA synthesis in vitro by isolated erythroleukemic cell nuclei: direct evidence for increased transcription during erythroid differentiation.

Abstract: Murine erythroleukemic cells accumulate cytoplasmic globin mRNA during differentiation induced in tissue culture by dimethyl sulfoxide. Cellular accumulation of globin RNA may reflect transcriptional activation of the globin genes and/or posttranscriptional stabilization of globin RNA during differentiation. To evaluate possible transcriptional controls directly, globin RNA synthesis by isolated erythroleukemic cell nuclei was studied.Conditions were established for optimal nuclear RNA synthesis in vitro in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Previous studies have shown and our results confirm that induction of MEL cells with DMSO is accompanied by a decrease in transcriptional activity (Orkin and Swerdlow 1977;Patel and Lodish 1984). Transcriptional output, measured in terms of total yield of TCA-precipi- table counts, dropped greater than 50% from day 0 to day 3 ( Fig.…”
Section: Changes In Transcription Rate During Mel Cell Inductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous studies have shown and our results confirm that induction of MEL cells with DMSO is accompanied by a decrease in transcriptional activity (Orkin and Swerdlow 1977;Patel and Lodish 1984). Transcriptional output, measured in terms of total yield of TCA-precipi- table counts, dropped greater than 50% from day 0 to day 3 ( Fig.…”
Section: Changes In Transcription Rate During Mel Cell Inductionsupporting
confidence: 79%
“…Induction is most notably characterized by a marked increase in globin gene transcription and accumulation of globin mRNA as has been reported by a number of independent investigators (Aviv et al 1976;Curtis and Weissmann 1976;Nudel et al 1977;Orkin and Swerdlow 1977;Lowenhaupt et al 1978;Hofer et al 1982). Our results show that even though the total transcriptional output of the cell is drastically reduced during induction, globin gene transcription increases greater than 40-fold.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In these studies, cloned globin genes are stably introduced into mouse erythroleukemia (MEL) cells which are derived from adult hematopoietic precursor cells transformed with the Friend virus complex (19; see reference 36 for review). Treatment of these cells with dimethyl sulfoxide (DMSO) or a variety of other chemical inducers leads to a series of morphological and biochemical modifications that mimic events in normal erythroid cell differentiation (19,36), including a dramatic increase in the rate of transcription of adult globin genes (8,29,49). When cloned mouse or human ,-globin genes are introduced into MEL cells by DNA-mediated gene transfer, they are coregulated with the endogenous mouse globin genes (8,60).…”
mentioning
confidence: 99%
“…Treatment of MEL cells with hexamethylene bis-acetamide (HMBA) or DMSO results in high-level induction of erythroid genes, including β-globin, and eventual terminal differentiation (50,51). The expression of EKLF, GATA-1, and importantly, HIRA proteins, are stable during the differentiation of MEL cells (Fig.…”
Section: Significancementioning
confidence: 99%